Cisco CallManager Fundamentals, Second Edition - Alexander, John; Pearce, Chris; Smith, Anne; Whetten, Delon (Cisco Press, 2005)
Exposes the inner workings of Cisco CallManager to help you maximize your Cisco IP Communications solution Read new content on QSIG, SIP trunks, video support, hunt lists and line groups, time-of-day routing, and new features added in CallManager releases 3.2, 3.3, 3.4, 4.0, and 4.1 Review content from the first edition that has been fully revised and updated to CallManager release 4.1 Learn how to deploy and manage a CallManager solution Understand the components that make up CallManager call routing through the use of basic to advanced examples that solve enterprise call routing problems Gain a full understanding of how CallManager manages media resources and processes information for conferencing, transcoding, annunciation, and more Learn detailed information about North American and international dial plans, trunk and station devices, media resources, and much more Cisco CallManager Fundamentals, Second Edition, provides examples and reference information about Cisco® CallManager, the call-processing component of the Cisco IP Communications solution. Cisco CallManager Fundamentals uses examples and architectural descriptions to explain how CallManager processes calls. This book details the inner workings of CallManager so that those responsible for designing and maintaining a Voice over IP (VoIP) solution from Cisco Systems® can understand the role each component plays and how they interrelate. This book is the perfect resource to supplement your understanding of CallManager. You'll learn detailed information about dial plan management and call routing, hardware and software components, media processing, call detail records, system management and monitoring, and the history of CallManager. The authors, all members of the original team that developed and implemented the CallManager software and documentation from its early stages, also provide a list of features and Cisco solutions that integrate with CallManager. This second edition of Cisco CallManager Fundamentals covers software releases through release 4.1. With this book, you will gain a deeper understanding of the system and find answers to questions not available in any other source. This book is part of the Cisco Press® Fundamentals Series. Books in this series introduce networking professionals to new networking technologies, covering network topologies, example deployment concepts, protocols, and management techniques.